2016
DOI: 10.2105/ajph.2015.303001
|View full text |Cite
|
Sign up to set email alerts
|

Public Funding for Contraception, Provider Training, and Use of Highly Effective Contraceptives: A Cluster Randomized Trial

Abstract: Public funding and provider training substantially improve LARC access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 15 publications
2
35
0
Order By: Relevance
“…Given prior analyses showing the importance of funding for LARC use, 13,17 we assessed participant health insurance (public [Medicaid, other state program], private, no insurance, do not know) as well as 3 site-level funding policy variables: whether the site was in a state with a family-planning Medicaid expansion program, Medicaid coverage of abortion, and mandated private insurance contraceptive coverage. 18 …”
Section: Methodsmentioning
confidence: 99%
“…Given prior analyses showing the importance of funding for LARC use, 13,17 we assessed participant health insurance (public [Medicaid, other state program], private, no insurance, do not know) as well as 3 site-level funding policy variables: whether the site was in a state with a family-planning Medicaid expansion program, Medicaid coverage of abortion, and mandated private insurance contraceptive coverage. 18 …”
Section: Methodsmentioning
confidence: 99%
“…Although the challenges for current pediatricians to obtain IUD training are real, a cluster randomized trial of a 4-hour training for placement of LARC methods by family planning clinic providers showed substantial increases in LARC provision. 27 Medical educators should redouble efforts to provide trainees with opportunities to place IUDs and implants, and push for training in LARC procedures as standard for pediatric trainees.…”
Section: Discussionmentioning
confidence: 99%
“…However, disparities remain, especially for marginalized groups [25]. In the United States (US), the implementation of Affordable Care Act (ACA) indicated a significant result in increasing of use of overall contraceptive, in the use of Long-Acting Reversible Contraceptives (LARCs), in decreasing of the births, in reducing of the proportion of births from unwanted pregnancies, and in reducing an inequality among insured women [6,[26][27][28][29][30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…The JKN policy could increase LACs use, especially in the group who has subsidized health insurance and the Nusa-Maluku-Papua region, but an inequity has remained between urban and rural areas. Most studies indicated that health insurance had made a significant contribution to increasing of LACs use [6,[26][27][28][29][30][32][33][34][35][41][42][43][44][45][46]. The contribution of LACs use in the success of the family planning program is very crucial, but until 2016, LACs use coverage in Indonesia was only 18.72%.…”
Section: Discussionmentioning
confidence: 99%